2020
DOI: 10.21203/rs.2.19776/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astaxanthin-loaded polymer-lipid hybrid nanoparticles (ATX-LPN) Assessment of potential otoprotective effects

Abstract: Background Ototoxicity is one of the major side effects of platinum-based chemotherapy, especially cisplatin therapy. To date, no FDA approved agents to alleviate or prevent this ototoxicity are available. However, ototoxicity is generally believed to be produced by excessive generation of reactive oxygen species (ROS) in the inner ear, thus leading to the development of various antioxidants, which act as otoprotective agents. Astaxanthin (ATX) is an interesting candidate in the development of new therapies f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Several studies have reported that mechanotransducer (MET) channels mediate the entry of cisplatin into cochlear hair cells, but it remains unclear whether MET channels are blocked during that process. 30,46,53 A study using larval zebrafish confirmed that cisplatin-induced damage to the hair cells relies on functional MET channels. 19 Furthermore, the effect of platinum (II) complexes on adult zebrafish auditory system suggested that cisplatin, and to a limited extent phenanthriplatin, can induce hair cells loss in particular regions of the saccule but not the utricle, 56 suggesting either various regional susceptibility to cisplatin or its distinct diffusion or transport pattern.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have reported that mechanotransducer (MET) channels mediate the entry of cisplatin into cochlear hair cells, but it remains unclear whether MET channels are blocked during that process. 30,46,53 A study using larval zebrafish confirmed that cisplatin-induced damage to the hair cells relies on functional MET channels. 19 Furthermore, the effect of platinum (II) complexes on adult zebrafish auditory system suggested that cisplatin, and to a limited extent phenanthriplatin, can induce hair cells loss in particular regions of the saccule but not the utricle, 56 suggesting either various regional susceptibility to cisplatin or its distinct diffusion or transport pattern.…”
Section: Discussionmentioning
confidence: 97%
“…Overproduction of ROS can activate the signal transducer and activator of transcription 1 (STAT1), inducing the inflammation. 46 Previous studies have shown that ROS might induce autophagy, which, depending on the stimulation context, can promote either cell survival or lead to cell death. 54,55 The critical step responsible for the ototoxic properties of cisplatin is its transport inside the sensory cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation